Cardiovascular abnormalities in severe scrub typhus - Nadda, Nishant; Mahajan, Sanjay; Kaushik, Madan; Merwaha, Rajeev (International Journal of Research in Medical Sciences, 2019)
Background: Himachal Pradesh is an endemic area for scrub typhus. If not treated early, it can lead to life threatening complications, affecting various systems of the body. Hence, this study was done with an objective to study the cardiovascular abnormalities in patients of severe scrub typhus. Methods: Authors conducted a hospital-based study in Departments of Medicine and Cardiology, of a tertiary care hospital in Sub-himalayan region in patients of severe scrub typhus from June 2016 to May 2017. Results: Thirty-two (55%) patients were aged <60 years with female preponderance (72%). Electrocardiographic changes included sinus tachycardia in 56 (97%), axis deviation in 5(9%), ST-T changes in 3(5%) and atrial fibrillation in 1(2%). Echocardiographic changes included tricuspid regurgitation in 14(24%), pericardial effusion in 4(7%), myocarditis in 1(2%) and Regional wall motion abnormality in 1(2%). Left ventricular ejection fraction >45% in 47 (81%) and <45% in 11(19%). Fifty-one patients had hypotension at presentation and 49 (90%) of them improved. Interestingly, 10 of 11 patients with reduced EF (<45%) survived whereas 6 of total 7 patients, who died, had preserved EF (>45 %). Conclusions: Severe scrub typhus manifested with ST/T changes, myocarditis, pericardial effusion, arrhythmias, shock and patients with reduced EF on Echocardiography had better outcome.